The Combined Use of Terrestrial Laser Scanner and Handheld 3D Scanner for 3D Modeling of Piping Instrumentation at Oil and Gas Company - Irwan Gumilar; Farhan Farohi; Made Munarda; Brian Bramanto; Gusti Ayu Jessy Kartini (Journal of Engineering and Technological Sciences, 2022)
Three-dimensional (3D) models are indispensable in managing, operating, maintaining, and repairing piping instrumentation activities in oil and gas companies. 3D models are expected to provide more interactive and representative information according to actual objects. Several technologies that can be used to generate piping instrumentation 3D maps are Terrestrial Laser Scanner (TLS) and Handheld 3D Scanner (HS). This study aims to create a 3D model of piping instrumentation using a combination of TLS and HS and analyze the results of data validation used for modeling. The results showed that a 3D modeling of piping instrumentation could be generated accurately using a combination of TLS and HS technologies. Merging between the two data is carried out through a cloud-to-cloud registration process based on the geometry of the object by considering the selection of reference data, the similarity of the scale factor, the unit of measure, and the overlap of the two data. The registration error generated in combining these two methods is less than 0.003 m. The resulting model still has drawbacks, which is the absence of coding for the pipe caused by the unavailability of the Piping and Instrumentation Diagram (P&ID) during modeling. The geometric validation of the model size value using reference data and the field size has the largest absolute difference of 0.0034 m with an average absolute deviation of 0.0016 m.